Monet at Giverny : A Book of Days - Harris, Derek, author 566538 (London : Century, 1989)
The perfect gift for art lovers, or anyone with an appreciation for beautiful gardens, this lovely book of days collects delightful examples of Monet's favorite subject, his gardens at Giverny. 56 color illustrations.